An investigation performed in a Bangladeshi general hospital on the use of proton pump inhibitors drugs by patients - Sony Tahmina Akter; Alam Md Nur; Hoque Majedul M. (Hospital Pharmacology)
Introduction: Proton pump inhibitors (PPIs) are anti-ulcer drugs that have reportedly been used inappropriately in therapeutic settings, raising the risk of adverse effects, drug interactions , and costs. Aim: This study aimed to evto evaluate the inappropriate use of PPI medication and which category of PPIs frequently was used for patients in Bangladeshi hospitals. Material and Methods: A one month cross-sectional study was carried out in a tertiary care hospital to evaluate the kinds of PPI prescriptions, their appropriateness, and their tendency to be utilized among patients. Results: Among 298 patients interviewed,140 patients used PPIs inappropriately. The most common reasons for inappropriate use included gastric appetite (29.59%, 29 individuals) and nausea. Other reasons included (15%) no clear indication, (20%) gastric discomfort, (13.57%) asthma, and (8.57%) infections. Esomeprazole was the most prescribed PPI, used by 41% of patients, followed by omeprazole at 32%. Nearly 44% of the 140 patients exhibited a strong tendency to use PPIs. Conclusion: Important steps must be taken to ensure that PPIs are used properly, to increase knowledge, and implement educational TV programs that can reduce the risk of drug interactions, side effects, and unnecessary expenses.